2005
DOI: 10.1200/jco.2005.03.134
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Low Molecular Weight Heparin on Survival in Patients With Advanced Malignancy

Abstract: A brief course of subcutaneous low molecular weight heparin favorably influences the survival in patients with advanced malignancy and deserves additional clinical evaluation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
382
1
12

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 565 publications
(407 citation statements)
references
References 16 publications
(11 reference statements)
12
382
1
12
Order By: Relevance
“…These data extend previous observations that have implicated antimetastatic effects for heparin and HLGAGs in animal model systems (21)(22)(23)(24)(25)(26). Clinical studies have also indicated that heparin and HLGAGs may prolong survival of patients with cancer with solid tumors (3)(4)(5).…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…These data extend previous observations that have implicated antimetastatic effects for heparin and HLGAGs in animal model systems (21)(22)(23)(24)(25)(26). Clinical studies have also indicated that heparin and HLGAGs may prolong survival of patients with cancer with solid tumors (3)(4)(5).…”
Section: Discussionsupporting
confidence: 76%
“…Highly sulfated heparan sulfate glycosaminoglycans, such as heparin, are commonly used to prevent venous thromboembolism, which is a common complication in patients with cancer as well. Heparin and heparin-like glycosaminoglycans (HLGAGs) have also been shown to prolong survival of patients with cancer, suggesting an antimetastatic effect for these compounds (3)(4)(5). The applicability of heparin in cancer therapy is limited because of its strong anticoagulant activity, but HLGAGs with less undesired effects on blood coagulation have been developed.…”
Section: Introductionmentioning
confidence: 99%
“…Low molecular weight heparin (LMWH) may attenuate these events through multiple mechanisms, including 1) by directly inhibiting thrombin or other coagulation proteins by catalyzing antithrombin, 3 2) by indirectly inhibiting thrombin formation by stimulating the release of tissue factor pathway inhibitor, an effective inhibitor of TF-mediated coagulation, 3 and 3) by inhibiting VEGF-A. 3 growth in several cancers in early, 32,33 but not advanced disease. 21 We show that LMWH significantly reduced tumor cell proliferation and thrombin generation in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, the HB-EGF-induced proliferation of myeloma cells was inhibited by 46% with 0.1 IU/ml of heparin, which is in the range of therapeutic concentrations. One recent study has reported that a short-term treatment with heparin could improve the survival of patients with metastatic epithelial cancers (Klerk et al, 2005). One possible mechanism might be that heparin competes with HS for the binding of growth factors preventing their stimulatory effect on tumor cells.…”
Section: Discussionmentioning
confidence: 99%